PENDIDIKAN KARAKTER MENURUT KH. HASYIM ASY’ARI ( Perspektif Filosofis ) - Amin Nurbaedi (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2018)
Generally, the charachter building of the students is still extent of memorizing and introducing value, it has not exist yet in the level of appreciation of those values moreover to the level making of those value as personal commitments in life. The focus of this research were ( 1) how is profile and charachteristic of KH. Hasyim Asy’ari; (2)how is concept of charachter building according to KH Hasyim Asy’ari? How is the role of the teacher in charachter building based on  KH Hasyim Asy’ari view? Then also, how is the good  stretegy accoroding to KH. Hasyim Asy’ari? This research used library research. The primary of the data was personal document,i.e Adab al-‘Alim wa al-Muta’allims’ book and  the secondary data was derivation from scientific publication such as books, jurnal, article, and also the result of other researches that suitable with concept of charachter building. The data is conducted by using documentation, and indentifying the text from Adab al-‘Alim wa al-Muta’allim’s book and also the others creation suitable with charachter builing. The data was analyzed by using content analysis in inductive approach. The phase of this research was done in some phase, namely pre research, field work, analyzing the data includes organizing of the data, validaty of data, interpretation and giving the meaning, and research report. This research found that (1) the charachter of students according to K.H. hasyim Asy’ari in Adab al-‘Alim wa al- Muta’allim’s book can be classified into 3 steps, they are : a. Attitude or charachter that must be had by students and teachers. b. Teacher and the students must effort become people that have special charachteristic, c teacher must have strategy in teaching and students mus have tstrategy in learning. Those steps have some indicators that suitable with teacher’s competency according to UU Sisdiknas in 2003 and 18 charachaters according to develpoment of cuccriculum center and culture eductaion and people’s charachter; (2) Relevansi of charachter building according to K.H. Hasyim Asy’ari and the context of charachter building of indonesian, such as : meaning and aims of charachter building, good value for teacher and students, background of arguments of charachter building, character building’s methode, media of charachter building, and evaluation of charachter building.